2016
DOI: 10.1088/1748-9326/11/9/095009
|View full text |Cite
|
Sign up to set email alerts
|

Reserves and trade jointly determine exposure to food supply shocks

Abstract: While a growing proportion of global food consumption is obtained through international trade, there is an ongoing debate on whether this increased reliance on trade benefits or hinders food security, and specifically, the ability of global food systems to absorb shocks due to local or regional losses of production. This paper introduces a model that simulates the short-term response to a food supply shock originating in a single country, which is partly absorbed through decreases in domestic reserves and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 36 publications
3
100
0
Order By: Relevance
“…Indeed, some nodes (i.e., countries) are starting to show the first episodic signs of instability, particularly in water‐poor and trade‐dependent countries (Suweis et al, ). This analysis of the long‐term response to shocks is in agreement with the short‐term propagation of perturbations in the trade network during a food crisis (Marchand et al, ; Puma et al, ; Tamea et al, ); both approaches have shown how the fragility of the coupled food‐demographic system has increased as an effect of the growing globalization of food through trade.…”
Section: Resilience In the Few Nexussupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, some nodes (i.e., countries) are starting to show the first episodic signs of instability, particularly in water‐poor and trade‐dependent countries (Suweis et al, ). This analysis of the long‐term response to shocks is in agreement with the short‐term propagation of perturbations in the trade network during a food crisis (Marchand et al, ; Puma et al, ; Tamea et al, ); both approaches have shown how the fragility of the coupled food‐demographic system has increased as an effect of the growing globalization of food through trade.…”
Section: Resilience In the Few Nexussupporting
confidence: 82%
“…This phenomenon establishes long‐distance teleconnections and interdependencies between crop production areas and global demand (Rulli & D'Odorico, ). On the receiving end, the globalization of food markets and the vulnerability and exposure to food crises and climatic shocks (Marchand et al, ; Seekell et al, ) make transnational investments in agricultural land a strategic food security priority in order to gain resilience through diversification of the agricultural regions that importer and investor countries rely on. Interestingly, most target countries are endowed with productive agricultural land that in some regions require relatively small amounts of irrigation water (Figure ) and are not affected by aridification under climate change scenarios (Chiarelli et al, ).…”
Section: Globalization Of Food and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Shocks are transmitted through global grain trade networks (Fair et al, 2017;Puma et al, 2015) and the entire food (Distefano et al, 2018;Ercsey-Ravasz et al, 2012) and virtual water (Tamea et al, 2016) trade networks. Recent work has shown that grain stores buffer production shortfalls, making them important to consider in assessments of food network reliability (Marchand et al, 2016). An empirical assessment of grain and virtual water stocks will enable future evaluations of shock transmission in the global food systems to add this component (Lant et al, 2018).…”
Section: 1029/2018wr024292mentioning
confidence: 99%
“…The global system of food production and trade is complex and drives interdependency among heterogeneous regions, meaning that socio-economic or environmental changes in one part of the globe can have cascading impacts for food and water security throughout the world (Fig. 1b) (D'Odorico et al, 2010;Marchand et al, 2016;Young et al, 2006). Equally, there is interdependency across sectors with Figure 1.…”
Section: Introductionmentioning
confidence: 99%